投资环境的决定因素与政府吸引外资工作 = The decisive factor to investment environment and the local government's work to draw foreign capital - 魏增新 Wei, Zengxin (2008)
This thesis summarizes eight factors which influence investment environment that China's local governments try to improve to attract foreign investment . These factors are economic growth and total account, cultural background, foreign law, human resources, natural endowments, role of government, market system and infrastructure. The research method includes specialist visits and case studies. This thesis particularly analyses the factors' role of investment environment in economic theory and set up the theory frame. We put forward our suggestion in improvng investment for government by the research results.